ENGLISH EDUCATION MASTER STUDENTS’ PERCEPTIONS ON ONLINE LEARNING DURING COVID-19 PANDEMIC - Wijaya, Kristian Florensio (Sanata Dharma University Yogyakarta, 2022)
ELT enterprises are always ever-changing in these recent years due to the learners’ learning needs, preferences, interests, and proficiency. This progressive change is noticeable during this covid-19 pandemic where all educational institutions are commissioned their learners to study from home with the support of technological interfaces. This current small-scale qualitative study was an attempt to discover the specific perspectives upheld by English Education Master Students concerning the internalization of online EFL learning activities during these recent 2 year periods. To fulfill this research objectivity, the narrative inquiry was employed to fully attain the authentic data derived from the research participants manifested in the form of stories. In the short-term data gathering processes, 5 open-ended written narrative inquiry questions were distributed to 2 English Education Master Students of Sanata Dharma University, batch 2020. Anchored on the obtained research results, online EFL learning activities are quite beneficial in promoting more fruitful learning outcomes and embracing learners’ learning pace in absorbing the imparted learning materials. Hence, it is worth highlighting that this learning method is appropriately suitable for nowadays target language learning venture due to its practicality and feasibility. Some specific suggestions were also depicted in the last section.